Role of V2O5 coating on LiNiO2-based materials for lithium ion battery - Xiong, Xunhui; Wang, Zhixing; Yan, Guochun; Guo, Huajun; Li, Xinhai (Journal of power sources, 2014)
X-ray diffraction (XRD), transmission electron microscope (TEM), energy dispersive spectrometer (EDX) and X-ray photoelectron spectroscopy (XPS) are used to demonstrate that V2O5 is successfully coated on LiNiO2-based materials. The V2O5 layer will react with Li impurities on surface, which will reduce the pH value and rapid moisture uptake ability of LiNiO2-based materials. Cells tests indicate that V2O5-coating layer works as HF inhibitor and/or HF scavenger, which contributes a significant improvement in cycling performance and storage characteristics in electrolyte. In the mean time, V2O5 acts as isolating layer when cathode material contacts with electrolyte especially cycling at high voltage. Structural analysis shows that V2O5-coating layer has more advantage over other oxide coating in delaying Ni3+/Ni2+ transformation and lithium extraction from bulk surface, which benefits from the properties of V2O5 reacting with LiOH/Li2CO3 impurities on surface.